Critical approaches to Joseph Conrad - Szczeszak-Brewer, Agata (University of South Carolina Press, 2015)
"Critical Approaches to Joseph Conrad is a collection of essays directed to both new and experienced readers of Conrad. The book takes into account recent developments in literary theory, including the prominence of ecocriticism, ecopostcolonial approaches, and gender studies. Editor Agata Szczeszak-Brewer offers a comprehensive and comprehensible introduction to Conrad's most popular texts, also addressing the most recent academic debates as well as the conversations about narrative and genre in Conrad's canon. Students and scholars of Conrad, twentieth-century literature, and modernism will appreciate the clear, accessible prose by nineteen internationally recognized contributors who approach Conrad in different ways, from postcolonial and ecocritical perspectives, through explorations of gender, to psychoanalysis, narrative theory, and political analysis. Beginning with a biographical introduction by Szczeszak-Brewer, the collection offers an essay outlining the cultural and historical contexts that influenced Conrad's fiction and an essay on reception of Conrad's work. Following that, contributors provide critical approaches to Heart of Darkness, Lord Jim, Typhoon, Nostromo, The Secret Agent, The Secret Sharer, and Under Western Eyes. In these sections scholars offer insights about complex issues in Conrad's fiction, ranging from the study of specific literary tools and narrative development in his books to the political theories in Conrad's portrayal of the threat of terrorism and violent revolutions"--